2012
DOI: 10.1038/nature11779
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small RNA pathway genes using patterns of phylogenetic conservation and divergence

Abstract: Genetic and biochemical analyses of RNA interference (RNAi) and microRNA (miRNA) pathways have revealed proteins such as Argonaute/PIWI and Dicer that process and present small RNAs to their targets. Well validated small RNA pathway cofactors, such as the Argonaute/PIWI proteins show distinctive patterns of conservation or divergence in particular animal, plant, fungal, and protist species. We compared 86 divergent eukaryotic genome sequences to discern sets of proteins that show similar phylogenetic profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
188
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(195 citation statements)
references
References 28 publications
6
188
0
Order By: Relevance
“…Together with other reports, our study reveals an evolutionarily conserved scheme in which splicing factors modulate RNAi in a manner independent of their pre-mRNA splicing activities (26)(27)(28)(29)(30). In an interesting reversal, recent studies report that small RNAs and components of the RNAi machinery modulate pre-mRNA splicing in flies and mammals (41,42).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Together with other reports, our study reveals an evolutionarily conserved scheme in which splicing factors modulate RNAi in a manner independent of their pre-mRNA splicing activities (26)(27)(28)(29)(30). In an interesting reversal, recent studies report that small RNAs and components of the RNAi machinery modulate pre-mRNA splicing in flies and mammals (41,42).…”
Section: Discussionsupporting
confidence: 83%
“…For example, mutations in genes encoding a subset of splicing factors impair RNAi-mediated heterochromatin formation and transcriptional silencing in Schizosaccharomyces pombe (26). In addition, genome-wide RNAi screens of Caenorhabditis elegans and cultured Drosophila cells, as well as a recent analysis of phylogenetic conservation of candidate RNAi factors, indicated that specific splicing factors are required for RNA-mediated gene silencing (27)(28)(29)(30). Furthermore, SNR-3, the C. elegans homolog of SmD1, a core protein of the Drosophila small nuclear ribonucleoprotein particle (snRNP), associates with DCR-1 (31).…”
mentioning
confidence: 99%
“…Previously, we reported the identification of several signaling kinases, including the conserved serine/threonine kinase, casein kinase II (CK2), in a genome-wide RNAi screen for candidate factors involved in small RNA-mediated silencing in C. elegans (31,32). In this study, we characterize the role of CK2 as a positive regulator of miRISC activity in C. elegans.…”
mentioning
confidence: 99%
“…RNA interference (RNAi), a sequence-specific gene silencing mechanism induced by double-stranded RNA (dsRNA), has emerged as a promising therapy for combating cancer (19,33,34). The RNAi effect can be mediated with short interfering RNA (siRNA), which is a short, double stranded RNA with 21-23 base pairs (35), or, as recently demonstrated, with short hairpin RNA (shRNA) (36). Although siRNA and shRNA elicit comparable gene silencing effects in RNAi experiments, chemically synthesized shRNA represents significant advantages over siRNA.…”
Section: Discussionmentioning
confidence: 99%